2019
DOI: 10.1177/1071100719850806
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety Effect on Patient-Reported Outcomes Following Foot and Ankle Surgery

Abstract: Background: Preoperative emotional distress has been shown to negatively influence joint arthroplasty and spine surgery, but limited data exist for foot and ankle outcomes. Emotional distress can be captured through modern tools like the Patient-Reported Outcomes Instrument Measurement System (PROMIS) anxiety domain. We hypothesized that patients with greater preoperative PROMIS anxiety scores would report greater pain and less function after foot and ankle surgery than patients with lower preoperative anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Future studies should include treatment with other opioids. Postoperative pain and opioid consumption are also influenced by a patient’s psychological factors, the preoperative experience of pain, and the preoperative use of opioids [ 49 – 51 ]. It is difficult to evaluate these factors accurately in retrospective investigations; therefore, to comprehensively assess the factors affecting postoperative opioid dosage, it is necessary to add these predictive factors to future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include treatment with other opioids. Postoperative pain and opioid consumption are also influenced by a patient’s psychological factors, the preoperative experience of pain, and the preoperative use of opioids [ 49 – 51 ]. It is difficult to evaluate these factors accurately in retrospective investigations; therefore, to comprehensively assess the factors affecting postoperative opioid dosage, it is necessary to add these predictive factors to future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Beleckas et al defined clinically significant anxiety as a score of 62 or higher on the Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety Scale, 16 and Nixon et al defined a PROMIS Anxiety score of 59.4 or higher as anxiety. 17 Lee et al evaluated level of anxiety using a visual analog scale of anxiety (VAS-anxiety) and defined preoperative anxiety as a score of 1or higher on the VAS-anxiety Scale. 18 Hampton et al classified the HADS-Anxiety subscale (HADSA) scores of 8 to 10 as borderline abnormal and scores of 11 to 21 as abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…A study using the PROMIS Anxiety evaluation tool among patients treated for various diseases of the upper extremities reported that the prevalence of anxiety was 16.6% 16 and a study using the same evaluation tool in patients who underwent foot and ankle joint surgery reported that 28.8% of all patients showed anxiety. 17 A study using the VAS-anxiety evaluation tool in patients who underwent lumbar surgery reported that preoperative anxiety (point 0 or higher) was observed in 87% of all patients. 18 In a study evaluating the level of anxiety in patients with hip joint disease, it was reported that 4.3-43.8% of patients showed an abnormal level of anxiety depending on the disease, and 13.1% of patients showed an abnormal level of anxiety overall.…”
Section: Discussionmentioning
confidence: 99%
“…Also, evidence suggested that the preoperative anxiety anticipates worse pain and performance conditions in early surgical follow-up. Therefore, measures to reduce preoperative anxiety can help identify high-risk patients in terms of poorer surgical outcomes (Nixon et al, 2019). In the investigation of effects of spirituality and spiritual health on anxiety, spiritual factors predicting anxiety have shown that spiritual health can predict 39.1% of overt anxiety and 37.9% of covert anxiety in adults.…”
Section: Discussionmentioning
confidence: 99%